Molecular and Serological Investigation of Equine Herpesvirus Type 1 (EHV-1) and Type 4 (EHV-4) in Horses In Ibagué, Tolima - Julieth Michel Petano-Duque; Edwin Urueña-Martinez; Laura Liliana Cabezas-Callejas; Jorge Perilla-Amaya; Valentina Rueda-García; Iang Schroniltgen Rondón-Barragán; Ricaurte Lopera-Vásquez (Veterinary Medicine International)
EHV-1 is one of the most prevalent viral pathogens in horses; however, its prevalence is not well defined by cross-reactions of serological tests. Thus, this study aims to determine EHV-1/-4 prevalence in Colombian creole horses from Ibagué, Tolima, using molecular techniques, as well as to determine possible risk factors associated with viral infection. A cross-sectional study was carried out in 110 equines blood, serum, and semen samples from Ibagué, Tolima. Antibodies against EHV-1/-4 were determined through indirect ELISA. EHV-1 was detected by amplifying the glycoprotein H gene through heminested PCR, and risk factors were calculated with chi-square, odds ratio, and fisher test. EHV-1/-4 antibodies were found in 11.8% of the horses. Moreover, the presence of EHV-1 and EHV-4 was determined in blood, serum, and semen of healthy clinical equines, with a prevalence infection in horses of 43.36% for EHV-1 and 2.7% for EHV-4. Sex, age, births number, abortions, natural breeding, and artificial insemination did not show significance as risk factors. This study determined a high prevalence of EHV-1 and low prevalence of EHV-4 in horses from Ibagué, Tolima. Furthermore, the possibility of finding the infectious agent in blood, serum, and semen was demonstrated. We recommend the use of blood and serum samples for virus detection and the development of new studies to assess EHV-1 infection feasibility in venereal transmissions.